The Effect of the Completeness of Electronic Inpatient Medical Summaries on the Accuracy of Medical Record Quality at Purwokerto Islamic Hospital - Senja, Shafa Mutiara Aulia; Romodon, Dion (Universitas Muhammadiyah Sidoarjo, 2024)
Background: An electronic medical summary is a concise overview provided by healthcare professionals, particularly doctors, during a patient's treatment period until discharge, whether the patient is alive or deceased. The completeness of electronic medical records is crucial as it impacts the quality of hospital services; incomplete data entry can affect the quality of medical records and the services provided by the hospital.Objective: This study aims to determine the effect of the completeness of electronic medical summaries on the accuracy of medical record quality at Purwokerto Islamic Hospital.Methodology: This research uses a quantitative approach with cross-sectional data collection and a descriptive correlation design. The study sample consists of 89 electronic medical summary forms for inpatient care, selected using simple random sampling. The data was analyzed using the Chi-square test.Results: The study found that the completeness of electronic medical summaries was 89%, while the incompleteness rate was 11%. The accuracy rate was 84%, with an inaccuracy rate of 16%. The primary cause of incomplete electronic medical summaries was missing patient diagnoses. The Chi-square test results showed a p-value of 0.001 (p 0.05). Based on this p-value, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, indicating that there is a significant effect of the completeness of electronic medical summaries on the accuracy of medical record quality.